PENGARUH PERILAKU HEDONIC SHOPPING MOTIVATION TERHADAP COMPULSIVE BUYING PADA WANITA DI BANDA ACEH YANG MELAKUKAN PEMBELIAN SECARA ONLINE - Muhammad Wahyu Santoso; Rizki Amalia (Departemen Manajemen, 2020)
The study is to know about the effect from hedonic shopping motivation on compulsive buying behavior in women in Banda Aceh who make online purchases. The sample used in this study was 150 women who had made online purchases in Banda Aceh. The data’s tools which used for this srudy were questionnaires distributed through Google forms. The technique of sampling is Non-probability Sampling, which’s a sampling technique that does not provide random chance. Multiple linear regression (Multiple Linear Regression) used for analysis method to describe the effect from all variables involved.The independent variable show us the result variables Relaxation Shopping and Idea Shopping had significant effect and positive (sig 0.05) on Compulsive Buying. While Adventure Shopping and Value Shopping are not significant (sig 0.05) against Compulsive Buying with a regression coefficient of Relaxation Shopping (X1) 0.205, Idea Shopping (X2) 0.271, Adventure Shopping (X3) 0.189, and Value Shopping (X4)0.145.